HYDROALLANTOIS INA GOAT ( CAPRA HIRCUS)- A CASE REPORT - TRIPATHI, ASHUTOSH; MEHTA, J S (The Indian Journal of Animal Reproduction, 2023)
A rare case of hydroallantois and its clinical management in a full term pregnant 2½ year old pleuriparous goat having symptoms of anorexia, respiratory distress, bilateral abdominal distension, reluctant to stand and move is reported. Abdominal ultrasonographic examination revealed presence of large volume of fluid with enlarged but reduced numbers of cotyledons. Abdominocentasis was performed for relieving respiratory distress; fluid therapy along with prostaglandin (cloprostenol sodium) and dexamethasone was administered for induction of parturition and managing the shock. Approximately 13 liters of allantoic fluid was removed in 2 consecutive days and two fetuses (one live and one dead) without any observable congenital defect were delivered by gentle traction. Parentral as well as intra-uterine antibiotic coverage along with oral ecbolic (exapar liquid) was given for 5 days. Placentas were expelled out after 48 hours.
Keywords: Hydrallantois; Goat; Placental dropsy; Ultrasonography; Clinical management